A72 NUTRITIONAL INDICATORS AND POSTOPERATIVE OUTCOMES IN INFLAMMATORY BOWEL DISEASE: THE NSQIP SURGICAL COHORT. (15th March 2019) - Du, L; Jackson, T D; Chong, R Y; Nguyen, G C
Abstract: Background: The inflammatory bowel diseases (IBD), which include Crohn's disease (CD) and ulcerative colitis (UC), frequently lead to disease complications that require bowel surgery. Because of involvement of the intestines and increased catabolism due to inflammation, IBD patients, particularly those with ileal Crohn's disease, are susceptible to protein energy malnutrition (PEM). These individuals may be at increased risk of infection and poor wound healing, amongst other complications, that may in turn predispose to increased postoperative morbidity and mortality. Aims: The purpose of this study is to assess the prevalence of malnutrition in surgical IBD patients and its impact on postoperative outcomes including mortality, infectious complications, need for blood transfusion, non-septic complications, and rate of subsequent unplanned operations. Methods: The American College of Surgeon's National Surgical Quality Improvement Program (ACS-NSQIP) was created to measure short-term surgical outcomes and evaluate their predictors. Clinical information was prospectively collected from patients at participating hospitals who are at least 15 years old. We used ICD-9 codes to identify individuals undergoing IBD-related surgery between 2005 and 2012 with a diagnosis of Crohn's disease (555.x) or ulcerative colitis (556.x). Results: We identified 10, 913 IBD patients (6, 082 Crohn's disease and 4, 831 ulcerative colitis) who underwent bowel surgery. The prevalence of modest and severe hypoalbuminemia was 17% and 24%, respectively. 30-day mortality was higher in Crohn's patients with modest and severe hypoalbuminemia, compared to those with normal albumin levels preoperatively (0.7% vs. 0.2%, P<0.05; 2.4% vs. 0.2%, P<0.01); the same was true for patients with UC with modest and severe hypoalbuminemia (0.9% vs. 0.1%, P<0.01; 5.6% vs. 0.1%, P<0.01). Second, overall infectious complications were more common in the presence of severe hypoalbuminemia for CD (20% vs. 13%, P<0.01). and UC (28% vs. 15%, P<0.01) patients. Third, our study found that preoperative hypoalbuminemia was associated with an increased risk of need for blood transfusion as well as non-septic complications, including cardiac, neurologic, respiratory, renal, and thromboembolic complications. Lastly, the rate of return to the operating room for surgery within 30 days was higher amongst those with severe hypoalbuminemia for both CD (8.7% vs 6.3%, P<0.01) and UC (13% vs 6.8%, P<0.01). Conclusions: This study has established the association between preoperative hypoalbuminemia and short-term post-operative outcomes in IBD patients. When possible, attempts at nutritional optimization pre-operatively should be made. In cases where pre-operative hypoalbuminemia cannot be corrected, increased vigilance should be exercised to carry out process measures to mitigate post-operative complications. Funding Agencies: None